Upaya Penanganan Dermatitis Kontak Iritan pada Ibu Rumah Tangga Usia 48 Tahun melalui Pendekatan Kedokteran Keluarga di Puskesmas Lhoksukon - Ilhami Zalianty; Noviana Zara (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
Patient Mrs. N, a 48 year old woman, presented to the Lhoksukon Community Health Center’s geriatric clinic with a complaint of itching that began approximately 5 months ago and has worsened over the past month. Lesions were found on her hands and feet. The initial symptoms appeared after the patient was exposed to floodwaters; subsequently, the symptoms worsened, particularly after washing or performing household chores. Primary data were obtained through self-reporting, physical examination, home visits, completion of the family folder, and completion of the patient’s medical record. Patient assessment was conducted based on a holistic diagnosis encompassing quantitative and qualitative evaluations of the initial, ongoing, and final stages of the visit. Interventions provided included pharmacological therapy and education regarding the causes of Irritant Contact Dermatitis, the importance of maintaining skin cleanliness and moisture, and efforts to avoid triggering factors such as exposure to detergents, irritants, and prolonged contact with water. Education was also provided to encourage the patient to adopt clean and healthy lifestyle behaviors to prevent recurrence and worsening of the patient’s skin condition.